Longitudinal Metabolomics Reveals Ornithine Cycle Dysregulation Correlates With Inflammation and Coagulation in COVID-19 Severe Patients - Li, Tao; Ning, Nianzhi; Li, Bo; Luo, Deyan; Qin, Enqiang; Yu, Wenjing; Wang, Jianxin; Yang, Guang; Nan, Nan; He, Zhili; Yang, Ning; Gong, Saisai; et al. (Frontiers in Microbiology, 2021)
COVID-19 causes a severe disease to humans, as highlighted by the current global pandemic. Several studies about the metabolome of the COVID-19 patients have exhibited metabolic disorders and some potential diagnostic markers during disease progression. However, the longitudinal changes of metabolomics in COVID-19 patients, especially the association with disease progression, are unclear to date. Here, we systematically analyzed the dynamic changes of the serum metabolome of COVID-19 patients, demonstrating that most of the metabolites were not recovery at 1-3 days before discharge. A prominent signature in COVID-19 patients was significantly regulated about the metabolites in amino acids, peptides, and analogues, involving nine essential amino acids, ten dipeptides, and four N-acetylated amino acids. The levels of twelve metabolites in amino acid metabolism, especially three ornithine cycle-metabolites, were significantly increased in severe patients than mild ones, mainly in the onset days 1-3 or 4-6. Integrating blood metabolomic, biochemical, and cytokine data, we uncovered a highly correlated network, including six cytokines, thirteen biochemical parameters, and forty-nine metabolites. Significantly, five ornithine cycle-related metabolites (ornithine, N-acetylornithine, 3-Amino-2-piperidone, aspartic acid, and asparagine) were highly correlating with "cytokine storms" and coagulation index. We discovered that the ornithine cycle dysregulation significantly correlated with inflammation and coagulation in severe patients, which may be a potential mechanism in COVID-19 pathogenicity. Our study provided a valuable resource for in-depth exploration of metabolic factors in COVID-19 patients, guiding metabolic recovery, understanding the pathogenic mechanisms, and devising drugs against SARS-CoV-2 infection.